Navigating Vulnerability and Integration: Refugee Resettlement from Rwanda to Third Countries under the Medical Needs Category - Ingunn Bjorkhaug; Kine Marie Baekkevold (Oxford University Press, 2025)
Resettlement is a limited resource available to only a fraction of refugees. Selection criteria, set by the United Nations High Commissioner for Refugees and receiving States, may impose conflicting demands on refugees to exhibit both vulnerability and integration potential to be chosen, a phenomenon termed “promising victimhood”. Drawing on empirical data from interviews with 21 personnel from the United Nations High Commissioner for Refugees and Save the Children International in Rwanda, this article explores how medical needs criteria impact the inclusion or exclusion of refugees for resettlement. It finds that the selection criteria favour refugees with treatable conditions and favourable prognoses, thereby excluding those with chronic or fatal illnesses or patients with poor life expectancy. The article argues that such criteria potentially undermine the humanitarian objectives of the resettlement programme by marginalising some of the most vulnerable individuals. It discusses the implications of these findings for global burden-sharing strategies and calls for strengthening the medical infrastructure in asylum countries. The article concludes by questioning whether resettlement, in its current form, can truly serve as one of the three durable solutions for refugees with medical needs, given that it remains an option for only a select few. CrossRef